Lungs in Heart Failure - Apostolo, Anna; Giusti, Giuliano; Gargiulo, Paola; Bussotti, Maurizio; Agostoni, Piergiuseppe (Pulmonary Medicine, 2012)
Lung function abnormalities both at rest and during exercise are frequently observed in patients with chronic heart failure, also in the absence of respiratory disease. Alterations of respiratory mechanics and of gas exchange capacity are strictly related to heart failure. Severe heart failure patients often show a restrictive respiratory pattern, secondary to heart enlargement and increased lung fluids, and impairment of alveolar-capillary gas diffusion, mainly due to an increased resistance to molecular diffusion across the alveolar capillary membrane. Reduced gas diffusion contributes to exercise intolerance and to a worse prognosis. Cardiopulmonary exercise test is considered the “gold standard” when studying the cardiovascular, pulmonary, and metabolic adaptations to exercise in cardiac patients. During exercise, hyperventilation and consequent reduction of ventilation efficiency are often observed in heart failure patients, resulting in an increased slope of ventilation/carbon dioxide (VE/VCO2) relationship. Ventilatory efficiency is as strong prognostic and an important stratification marker. This paper describes the pulmonary abnormalities at rest and during exercise in the patients with heart failure, highlighting the principal diagnostic tools for evaluation of lungs function, the possible pharmacological interventions, and the parameters that could be useful in prognostic assessment of heart failure patients.